Knowledge and practices of South African oral - Zara Chothia; Ntombizodwa R. Nkambule; Ahmed Bhayat; Mpho Morule (AOSIS, 2024)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 is a recently discovered virus responsible for causing coronavirus disease 19 (COVID-19). No study has been carried out on South African oral healthcare workers (OHCWs) regarding their knowledge and practices with regard to COVID-19 and its vaccine. Aim: This study aimed to determine the knowledge, attitudes and practices of South African OHCWs regarding COVID-19 and its vaccine. Method: This was a cross-sectional study, which utilised an online questionnaire. The link to the questionnaire was sent via email and social media platforms. There was a total of 8056 OHCWs, and a minimum sample size of 367 was required. All information was confidential and anonymous. Results: A total of 327 OHCWs participated with a mean age of 43 years (±12.23) and the majority (60%) being general dentists. Less than half (42%) had obtained additional postgraduate qualifications while 57% were employed in the private and 24% in the academic sectors. Almost two-thirds (60%) obtained a 'good' knowledge score. Overall, OHCWs displayed positive attitudes towards COVID-19 and the majority implemented appropriate infection control protocols at their place of work. The majority (87%) reported to be vaccinated and of those who did not vaccinate, 34% cited concerns about possible side effects as a reason for not vaccinating. Conclusion: Respondents displayed gaps in their knowledge. There was a positive attitude towards the prevention of COVID-19, and almost all participants reported to have implemented the necessary infection control methods. Contributions: This study's contribution to research was to identify gaps in the knowledge and practices of OHCWs with regards to COVID 19 and its vaccine. Once these gaps have been identified, measures will be put in place to address them.